State law and trade unions - Bhargava, P. P. (Jaipur, 2005)
Introduction of machinery has changed the industrial structure and the relationship of the master and the servant altogether. Gulf between the employer and the employees became wider and wider. Trade unions came on the scene. Industrial unrest began to raise its ugly head. The role and functions of trade unions got new dimensions. Government had to step in to maintain industrial harmony and peace. The working class became aware of its rights and began to raise organized voice against the atrocities of employers. Agitation for trade union regulation became the order of the day. Ultimately, Government made up its mind to enact legislation for the protection of trade union leaders and active trade unionists engages in the furtherance of bonafied and legitimate trade union activities. An attempt has been made to discuss critically legislative as well as voluntary efforts in the form of Code of Discipline and their impact on trade unionism at the state as well as national level thread and bare.
Keywords: Law